2016
DOI: 10.1190/tle35070600.1
|View full text |Cite
|
Sign up to set email alerts
|

Distributed vibration sensing for seismic acquisition

Abstract: Distributed vibration sensing (DVS), also known as distributed acoustic sensing (DAS), is a relatively new method for recording seismic data using a standard fiber-optic cable as the sensor. Although the dynamic range and noise floor of DVS systems are currently below those of industry-standard seismic sensors, usable seismic data can be obtained in downhole configurations, as this is the source and receiver configuration at which DVS is most sensitive. The use of DVS for more conventional land and marine seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although distributed vibration measurements are found to respond well to small, dynamic strains even in loose-tube packages (Mullens et al, 2010;Strong et al, 2009), it should be noted that the distributed vibration measurement is in fact a measure of dynamic axial strain (Dean et al, 2015(Dean et al, , 2016. As a result, the measurement is insensitive (Papp et al, 2016) to compressional acoustic waves arriving at right angles from the fiber axis.…”
Section: Development Of Bespoke Cables For Distributed Sensingmentioning
confidence: 98%
“…Although distributed vibration measurements are found to respond well to small, dynamic strains even in loose-tube packages (Mullens et al, 2010;Strong et al, 2009), it should be noted that the distributed vibration measurement is in fact a measure of dynamic axial strain (Dean et al, 2015(Dean et al, , 2016. As a result, the measurement is insensitive (Papp et al, 2016) to compressional acoustic waves arriving at right angles from the fiber axis.…”
Section: Development Of Bespoke Cables For Distributed Sensingmentioning
confidence: 98%
“…This time, Schlumberger's ‘heterodyne Distributed Vibration Sensing’ system (Dean et al . ) was mobilized. The parameters related to DAS processing, that is, time sampling rate, spatial sapling rate and GL, in Table are the field parameters for real‐time onsite quality control.…”
Section: Overview Of the Distributed Acoustic Sensing Vertical Seismimentioning
confidence: 99%
“…As field data examples demonstrated here and Dean et al . (), the selection of GL or GLs appropriate for the target of surveys improves data quality a lot. Optimum GL varies survey by survey; it is affected by signal frequency contents, subsurface velocity, the type and amount of noise.…”
Section: Gauge Length Optimizationmentioning
confidence: 99%
“…Daley et al (2013) demonstrated a field test of DAS seismic acquisition of borehole seismic data and land surface seismic data. Additionally, Dean et al (2016) discussed its applications to marine seismic acquisition. On the other hand, Lumens (2014) studied various applications of DAS in oil and gas wells.…”
Section: Introductionmentioning
confidence: 99%